Coumarins from the Roots of Angelica archangelica and Antibacterial Activity Against Methicillin Resistant Staphylococcus aureus (Dhaka University Journal of Pharmaceutical Sciences, 2022)
Angelica archangelica (Fam. Apiaceae) roots were extracted sequentially with n-hexane, dichloromethane (DCM) and methanol (MeOH) using a Soxhlet apparatus. The n-hexane and DCM extracts were fractionated by Vacuum Liquid Chromatography (VLC) over silica gel followed by Preparative Thin Layer Chromatography (PTLC) to yield two coumarins, osthol (1) and osthenol (2). However, the methanol extract was fractionated by solid-phase extraction using C18 cartridge followed by analysis of components by analytical High Performance Liquid Chromatography (HPLC) and purification by preparative High Performance Liquid Chromatography (HPLC) to give two coumarins, bergapten (3) and heraclenol (4) along with sucrose (5). Compounds were identified by a series of 1D (1H and 13C) and 2D (COSY, HSQC and HMBC) NMR spectroscopy and mass spectrometric analysis. The crude extracts (n-hexane, DCM, and methanol) and compound 1, were screened for antimicrobial activity against Gram-positive bacteria (Methicillin resistant Staphylococcus aureus, MRSA and Micrococcus luteus), Gram-negative bacteria, Pseudomonas aeruginosa, and a fungus, Candida albicans. The antimicrobial assays showed that the crude DCM and n-hexane extracts, alongside compound 1, largely inhibited the growth of the microorganisms at high concentrations. Compound 1, which was further tested for antibacterial activity against a series of clinical isolates of methicillin resistance Staphylococcus aureus, showed moderate level of activity against only one strain.Dhaka Univ. J. Pharm. Sci. 20(3): 275-281, 2022 (June) Centennial Special Issue